Implementation of the STEAM model in mathematics subjects to improve learning outcomes - Kardiana Metha Rozhana; Adi Tri Atmaja; Nathasa Pramudita Irianti; Nila Kartika Sari; Kardiana Zendha Avalentina (Jurnal Bidang Pendidikan Dasar, 2023)
The purpose of this research is to implement the STEAM learning model to improve the mathematics learning outcomes of fourth grade elementary school students. The method used is classroom action research with research procedures including implementation, among others, preparing action plans, implementing actions, observing, and reflecting. The results obtained in cycle 1 of the student's average score were only 58.5 with an incomplete scale and the need for improvement/reflection. After the action in cycle 1, cycle 2 found a significant increase in learning completeness, namely reaching 85.75. So it can be concluded that the STEAM learning model can be implemented in class IV in mathematics.